Android-based Geographic Information System for Worship Places in Fakfak Regency - Arridha, Riyadh; Magfirah, Titing; Hayunada, Carlina Dewi; Astuti, Diah (Politeknik Ganesha Medan, 2021)
The rapid development of technology greatly affects people's lives today, one of which in Fakfak City has all been entered by the development of information technology. Fakfak is one of the regencies on the Papua island, the people of Fakfak Regency highly uphold religious values ​​and it is proven by the motto